2022
DOI: 10.1007/s00253-022-12123-6
|View full text |Cite
|
Sign up to set email alerts
|

Life at the periphery: what makes CHO cells survival talents

Abstract: The production of biopharmaceuticals relies on robust cell systems that can produce recombinant proteins at high levels and grow and survive in the stressful bioprocess environment. Chinese hamster ovary cells (CHO) as the main production hosts offer a variety of advantages including robust growth and survival in a bioprocess environment. Cell surface proteins are of special interest for the understanding of how CHO cells react to their environment while maintaining growth and survival phenotypes, since they e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…We observed upregulated genes involved in the MAPK‐ERK and PI3K‐Akt signaling pathways at LP (Supporting Information: Figures S4 and S5 and Table S1). Whilst both the MAPK‐ERK and PI3K‐Akt signaling pathways participate in multiple biological processes and are key for cell function, a recent study showed that activation of these pathways supported cell growth and survival during the environmental conditioning during bioprocessing scale‐up (Jerabek et al, 2022). In addition, we found that both cell lines showed increased expression of transcripts linked to focal adhesion signaling (Supporting Information: Table S1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We observed upregulated genes involved in the MAPK‐ERK and PI3K‐Akt signaling pathways at LP (Supporting Information: Figures S4 and S5 and Table S1). Whilst both the MAPK‐ERK and PI3K‐Akt signaling pathways participate in multiple biological processes and are key for cell function, a recent study showed that activation of these pathways supported cell growth and survival during the environmental conditioning during bioprocessing scale‐up (Jerabek et al, 2022). In addition, we found that both cell lines showed increased expression of transcripts linked to focal adhesion signaling (Supporting Information: Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…A phosphoproteomic analysis of human cancer cells showed constitutive activation of the PI3K/Akt and MAPK/ERK signaling pathways as a driver of cell proliferation (Y. Y. Lee et al, 2013) and of genomic instability (Ma et al, 2018). A recent CHO cell surfactome revealed the enrichment of these two pathways in CHO cells (Jerabek et al, 2022), suggesting that cell surface receptors and associated ligands play fundamental roles in controlling the proliferative status of CHO cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation